Cowpea Mild Mottle Virus (CpMMV) infection and its effect to performance of South Korean soybean varieties - SUTRISNO SUTRISNO; HERU KUSWANTORO (Society for Indonesian Biodiversity, 2016)
Sutrisno, Kuswantoro H. 2016. Cowpea Mild Mottle Virus (CpMMV) infection and its effect to performance of South Korean soybean varieties. Biodiversitas 17: 129-133. Cowpea Mild Mottle Virus (CpMMV) is a very detrimental disease to soybean. This virus infection can cause yield reduction up to 56%. Introduction varieties can be served as alternative material in breeding program to develop resistant variety. This study aimed to evaluate the response of introduction soybean varieties from South Korea to the CpMMV infection. Ten South Korean soybean varieties and two check Indonesian soybean varieties were grown at ILETRI from August to November 2012. CpMMV infection was carried out by natural infection using whitefly (Bemisia tabaci) transmission. The results showed that the South Korean variety of Daemang-2 had lower leave malformation level than two Indonesian varieties. Varieties of Cheongja-3, Daemang, Daehwang, Daewon, Danweon, Geomjeong-3 Geonjeongsaeol produced grain yield that equal to Anjasmoro variety. Daepung was the most resistant to CpMMV than other varieties, but having low grain yield. Daemang-2 was the most tolerantÂ to CpMMV, because it still able to produce high grain yield although showing high leaf infection. These two varieties could be used as gene sources for resistant/tolerant to CpMMV in soybean breeding program.